2016
DOI: 10.1167/iovs.15-18403
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Photoreceptor Regeneration and Visual Acuity Following Surgery for Rhegmatogenous Retinal Detachment

Abstract: PURPOSE. The purpose of this study was to evaluate foveal regeneration and the association between retinal restoration and visual acuity following reattachment surgery for rhegmatogenous retinal detachment (RRD).METHODS. Twenty-nine eyes of 29 patients with successfully reattached macula-off RRD were retrospectively analyzed. We used spectral-domain optical coherence tomography to image macular regions and measure retinal thickness and Snellen chart visual acuity (VA) to evaluate best-corrected VA (BCVA) at 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
64
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 39 publications
6
64
1
2
Order By: Relevance
“…However, our results should be interpreted with caution. Contrary to other studies that reported the correlation between postoperative visual acuity and the integrity of outer retinal layer, [9][10][11]17,33 the EZ-RPE thickness (a parameter related to the outer retinal layer status used in this study) was not a significant contributing factor. Based on the results shown in Table 1, the EZ-RPE thickness was decreased in the RRD eyes compared with fellow eyes, both in the outer-retinal-defect group and the intact-outer-retina group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, our results should be interpreted with caution. Contrary to other studies that reported the correlation between postoperative visual acuity and the integrity of outer retinal layer, [9][10][11]17,33 the EZ-RPE thickness (a parameter related to the outer retinal layer status used in this study) was not a significant contributing factor. Based on the results shown in Table 1, the EZ-RPE thickness was decreased in the RRD eyes compared with fellow eyes, both in the outer-retinal-defect group and the intact-outer-retina group.…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous studies have reported the recovery of outer retinal thickness and photoreceptors over time after retinal detachment surgery in macula-off RRD. 10,11,17 Ra et al 17 used electroretinography and OCT to report a longterm increase in cone density and outer retinal layer thickness after buckling surgery for RRD. They divided EZ-RPE thickness into EZ-CIZ thickness and CIZ-RPE thickness and showed an increase in both of them 12 months postoperatively compared with 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RPE has a wide variety of function, as such nutrient supply, oxidative stress protection, phagocytosis, and secretion of survival signals for retinal cells [5]. In addition, RPE has a potential for regeneration [6,7]. The sequence of events leading to GA is the progression of large drusen to hyperpigmentation, followed by regression of the drusen, hypopigmentation and ultimately RPE cell death, leading to atrophic area of the retina underlying choroids [8].…”
Section: Discussionmentioning
confidence: 99%